2000
DOI: 10.1007/s002689910074
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Mortality, Survival, and Quality of Life after Resection for Gastric Cancer in the Elderly

Abstract: Although there were some studies on clinicopathologic characteristics, operative morbidity, and mortality in elderly patients with gastric cancer, no reports have specifically focused on survival and quality of life after resection. A total of 433 patients aged >/= 65 years (1987-1994) who underwent gastric resection for gastric adenocarcinoma were studied. Two groups were considered: patients aged 65 to 74 years and those > 74 years. Most of the patients (78.1%) had advanced diseases, and nearly half (41. 3%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
102
4
4

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(118 citation statements)
references
References 26 publications
(24 reference statements)
8
102
4
4
Order By: Relevance
“…Several reports have indicated that differentiatedtype or intestinal-type carcinomas are more common in older patients than in younger patients [3,[5][6][7][8][14][15][16]18,19]. Our study demonstrated that this tendency was clear, especially in early-stage cancer.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…Several reports have indicated that differentiatedtype or intestinal-type carcinomas are more common in older patients than in younger patients [3,[5][6][7][8][14][15][16]18,19]. Our study demonstrated that this tendency was clear, especially in early-stage cancer.…”
Section: Discussionsupporting
confidence: 64%
“…Previous reports have shown no significant difference in the incidence of lymph node metastasis between young and elderly patients with gastric cancer [3,[5][6][7][14][15][16][17][18][19]. Most of these reports did not take the clinical or pathological stage of the disease into account, and the results could not be simply compared with each other.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…In literature, controversy remains about the influence of chronologic age on the nodal status in gastric carcinoma. Most previous reports have negated a significant difference in the rates of LN metastasis between younger and elderly patients [37][38][39][40], whereas in cases of early gastric cancer several authors have reported a higher prevalence of LN involvement for elderly patients [41,42].…”
Section: Survival Analysismentioning
confidence: 96%